1999
DOI: 10.1021/jp991546e
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Boron−Ammonia Reactions

Abstract: The mechanisms of the reactions of a boron atom (2P) and of B2 (3Σg -) with ammonia were studied computationally at the hybrid DFT B3LYP/6-311++G(3df, 2p)//B3LYP/6-311++G(2d,p) level. The B and B2 insertions into NH bonds take place by initial formation of BNH3 and BBNH3 complexes. As found previously for methane and water, B2 also is more reactive than B with ammonia. The energy-rich boron atom insertion product, HBNH2, then gives the species HBNH2, H2BNH, HBNH, and BNH. These can react with a second boron at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Schleyer et al suggested that the reaction of ground state boron atoms [B( 2 P)] with ammonia leads to the formation of a weakly bound B-NH 3 complex, which isomerizes via a hydrogen shift to yield the HBNH 2 intermediate. 9 On the other hand, Andrews et al proposed an initial insertion of atomic boron of unknown electronic state into the nitrogen-hydrogen bond leading to the aminoborane, HBNH 2 intermediate. According to Schleyer et al, the HBNH 2 intermediate could isomerize to the thermodynamically less stable (∼19 kJ mol -1 ) borylamidogen radical (H 2 BNH) or fragmented via atomic and molecular hydrogen losses to imidoborane (HNBH) and iminoborane (BNH), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Schleyer et al suggested that the reaction of ground state boron atoms [B( 2 P)] with ammonia leads to the formation of a weakly bound B-NH 3 complex, which isomerizes via a hydrogen shift to yield the HBNH 2 intermediate. 9 On the other hand, Andrews et al proposed an initial insertion of atomic boron of unknown electronic state into the nitrogen-hydrogen bond leading to the aminoborane, HBNH 2 intermediate. According to Schleyer et al, the HBNH 2 intermediate could isomerize to the thermodynamically less stable (∼19 kJ mol -1 ) borylamidogen radical (H 2 BNH) or fragmented via atomic and molecular hydrogen losses to imidoborane (HNBH) and iminoborane (BNH), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21] In recent studies, Gwaltney and Head-Gordon 17 examined the structure by a series of coupled-cluster calculations. They found an asymmetric linear structure with a bond length difference between the two BN bonds of about 0.09 Å and a barrier of 161Ϯ 20 cm −1 .…”
Section: Introductionmentioning
confidence: 99%
“…33 In the photoelectron investigation, vibrational intervals in the X 2 ⌺ u + ground state were observed that matched those found in the matrix isolation study, but it was not necessary to invoke the existence of a cyclic form of the molecule. [35][36][37][38][39][40][41] While all of the computational methods show that the ground state of BNB is the linear X 2 ⌺ u + state, vibronic interaction with the à 2 ⌺ g + state introduces problems in estimating the frequency of the antisymmetric stretching motion. Herzberg-Teller vibronic coupling also transfers intensity from the electronically allowed à 2 ⌺ g + − X 2 ⌺ u + band system to the overtones of the u antisymmetric stretching vibration ͑ 3 ͒, causing the ͑0 0 0 3͒ and ͑0 0 0 5͒ levels to gain intensity in transitions from the ͑0 0 0 0͒ ground vibronic state, as observed in the matrix isolation spectra.…”
Section: Introductionmentioning
confidence: 99%